Microstructure of Compacted Loess and Its Influence on the Soil-Water Characteristic Curve. (8th January 2020) - Xie, Xiao; Li, Ping; Hou, Xiaokun; Li, Tonglu; Zhang, Guowei
Abstract : Soil-water characteristic curve (SWCC) is a key constitutive relationship for studying unsaturated soil, and as is known, microstructure of the soil has great influence on the mechanical behaviour of the soil. In this study, the wetting and drying soil-water characteristic curves (SWCCs) of loess compacted at three different water contents were measured using the filter paper method. And microproperties of compacted loess were obtained by the mercury intrusion method (MIP) and scanning electron microscope (SEM). Results show that the compaction water contents have significant influence on the SWCC and microstructure. The pore size distribution (PSD) curves have great differences in macropore range and are similar in micropore range. Loess compacted at optimum and dry of optimum are generally connected, while there are certain number of nonintruded pores in loess compacted at wet of optimum. The SWCC curves vary significantly in low suction (u a  − u w  < 1000 kPa) and tend to converge together in high suction (u a  − u w  ≥ 1000 kPa). Hysteresis in the SWCCs is more obvious for loess compacted at optimum and dry of optimum in the matric suction of 0∼100 kPa; however, there is a pronounced hysteresis for loess compacted at wet of optimum in full matric suction range. The characteristic of the SWCCs including their hysteresis can be well interpreted from the loess microstructure.